Pengaruh model project based learning berbantuan story maps terhadap kemampuan berpikir kreatif pada mata pelajaran Geografi siswa SMAN 7 Malang - Feny Panjerina; Fatiya Rosyida; Rudi Hartono; Purwanto Purwanto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2023)
The learning model that will be applied to students should be effective and interesting. One of the effective and interesting geography learning models is the project based learning model. The project based learning model is a learning model that makes products (projects) in a structured manner. This model can trigger students' curiosity to solve a problem at hand and can also develop students' creative thinking skills. This study aims to determine the effect of the project-based learning model assisted by story maps on the ability to think creatively in the geography subject of SMAN 7 Malang students. This research is a type of experimental quantitative research. Subjects in this study consisted of two classes, namely the experimental class and the control class XI IPS SMAN 7 Malang. The new thing in this research is the use of story map in this project based learning model, students can make maps in a simple and interesting way so as to improve students’ creative thinking skills. The results of the t-test (independent sample t-test) show that the significance value is 0.000 less than 0.05, which means that there is a significant affect of story map-assisted project based learning models on the ability to think creatively in geography subjects. A project based learning model assisted by a story map is better than students who only use a project based learning model. Model pembelajaran yang akan diterapkan kepada siswa sebaiknya efektif dan menarik. Salah satu model pembelajaran geografi yang efektif dan menarik ialah model project based learning. Model project based learning adalah model pembelajaran yang membuat produk (proyek) secara terstruktur. Model ini dapat memicu rasa ingin tahu siswa untuk memecahkan sebuah masalah yang dihadapi dan juga dapat mengembangkan kemampuan berpikir kreatif siswa. Tujuan riset ini adalah untuk mengetahui pengaruh model project based learning berbantuan story map terhadap kemampuan berpikir kreatif pada mata pelajaran geografi siswa SMAN 7 Malang. Riset ini merupakan jenis penelitian kuantitatif eksperimen. Subjek pada riset ini terdiri dari dua kelas yaitu kelas eksperimen dan kelas kontrol XI IPS SMAN 7 Malang. Hal baru pada riset ini yaitu penggunaan story map pada model project based learning ini siswa dapat membuat peta secara sederhana dan menarik sehingga meningkatkan kemampuan berpikir kreatif siswa. Hasil uji t (independent sample t-test) menunjukkan bahwa nilai signifikansi sebesar 0,000 kurang dari 0,05 yang artinya terdapat pengaruh yang signifikan model project based learning berbantuan story map terhadap kemampuan berpikir kreatif pada mata pelajaran geografi. Hal ini menunjukkan bahwa kemampuan berpikir kreatif siswa dengan model project based learning berbantuan story map lebih baik daripada siswa yang hanya menggunakan model project based learning.